MiniMovers: An Initial Pilot and Feasibility Study to Investigate the Impact of a Mobile Application on Children’s Motor Skills and Parent Support for Physical Development - Yajie Zhang; Nalda Wainwright; Jacqueline D. Goodway; Amanda John; Anna Stevenson; Kirsty Thomas; Sean Jenkins; Fatma Layas; Kate Piper (Children, 2024)
The MiniMovers (MM) APP combines motor development theory with creativity expertise and has been designed to provide parents with developmentally appropriate activities to support children’s motor skills. This study investigates how MiniMovers activities enabled parents to support their children’s physical development. Families participated in an 8-week MM programme of activities from the MM APP (Mini, Mighty and Mega levels), with pre- and post-intervention data collected using multiple tools (e.g., motion capture system, force plate, eye-tracking glasses, and videos). Mixed research methods were applied among children (N = 8; aged 21–79 months) and their parents, providing quantitative analysis on children’s performance (running, throwing, jumping, kicking, balancing and catching), as well as qualitative analysis on parents’ attitude and behaviour (two-weekly feedback surveys and interviews). Lab-based measures showed significant improvements in run time, underarm throwing distance, and horizontal jump distance. Test of Gross Motor Development-3 showed a significant gain in running, underarm and overarm throwing, horizontal jump and kicking. Further, developmental stages indicated significant improvements in running, kicking and catching. Parents reported increased enjoyment and knowledge, children’s enjoyment, independence and confidence. This pilot study provides support for the research and development of the MM App and suggests more research into the use of APPs to support home activities among families with young children.